2017
DOI: 10.1021/acs.biochem.7b00199
|View full text |Cite
|
Sign up to set email alerts
|

Olive Component Oleuropein Promotes β-Cell Insulin Secretion and Protects β-Cells from Amylin Amyloid-Induced Cytotoxicity

Abstract: Oleuropein, a natural product derived from olive leaves, has reported anti-diabetic functions. However, detailed molecular mechanisms for how it affects β-cell functions remain poorly understood. Here, we present evidence that oleuropein promotes glucose-stimulated insulin secretion (GSIS) in β-cells. The effect is dose-dependent and stimulates the ERK/MAPK signaling pathway. We further demonstrated that oleuropein inhibits the cytotoxicity induced by amylin amyloids, a hallmark feature of type 2 diabetes. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 21 publications
4
42
0
Order By: Relevance
“…PD results mostly from the aggregation of α-synuclein into intracellular Lewy bodies found in the neurons of the mesencephalic substantia nigra. Actually, olive polyphenols, notably OLE and its main metabolite, HT, have been reported to be effective against amyloid aggregation and the ensuing pathologic effects in T2DM [11,12], AD [13][14][15][16][17][18][19] and, possibly, in PD [20,21] and other amyloidoses. Plant polyphenols, including those enriched in EVOO, have also been reported to reduce insulin resistance and to improve impaired glucose homeostasis, two main signs of T2DM.…”
Section: Polyphenols: Important Players Of the Mediterranean/asian Dietsmentioning
confidence: 99%
“…PD results mostly from the aggregation of α-synuclein into intracellular Lewy bodies found in the neurons of the mesencephalic substantia nigra. Actually, olive polyphenols, notably OLE and its main metabolite, HT, have been reported to be effective against amyloid aggregation and the ensuing pathologic effects in T2DM [11,12], AD [13][14][15][16][17][18][19] and, possibly, in PD [20,21] and other amyloidoses. Plant polyphenols, including those enriched in EVOO, have also been reported to reduce insulin resistance and to improve impaired glucose homeostasis, two main signs of T2DM.…”
Section: Polyphenols: Important Players Of the Mediterranean/asian Dietsmentioning
confidence: 99%
“…Recently, several studies have suggested that natural phenolic compounds can interfere with the amyloid aggregation process both by affecting the amyloid intermediate formation and promoting the aggregation cascade towards nontoxic species [58,59]. In particular, the main phenolic compounds of extra-virgin olive oil, i.e., oleuropein aglycone (OleA) and its main metabolite, hydroxytyrosol (3,4-dihydroxyphenylethanol (HT), aside from their biological and pharmacological properties, have been shown to affect the amyloid aggregation process in different model proteins in vitro [12,[15][16][17][18][19][20][21]60]. Because only little information is available for HT compared to OleA, in this study, we tested the molecular effect of HT in the amyloid aggregation process of human insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HT has been shown to affect the amyloid aggregation process in hen egg white lysozyme, Aβ 1-42 , Amylin, Tau protein and α-synuclein [15][16][17][18]20,21]. In particular, HT has been suggested to interact with these amyloidogenic proteins and affect amyloid intermediate formation as well as promote the formation of off-pathway species unable to induce cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission Electron Microscopy (TEM) Analysis. TEM images were collected as previously described (Velander et al, 2016;Wu et al, 2017). Briefly, 30 µM human tau isoforms were incubated in 20 mM Tris-HCl, pH 7.4 for 10-12 days at 37 °C.…”
Section: Thioflavin-t Fluorescence Aggregationmentioning
confidence: 99%